The whites of their eyes - Clements, Andrew, 1949- (Benjamin Pratt & the Keepers of the School, 2012)
With a key to the Oakes School in his possession Benjamin, his friend Jill, and a new friend continue to seek ways to protect the school and their town but Lyman, the janitor and a spy, has new tricks up his sleeve.